Mutations in spalt cause a severe but reversible neurodegenerative phenotype in the embryonic central nervous system of Drosophila melanogaster. - Cantera, R.; Luer, K.; Rusten, T.E.; Barrio, R.; Kafatos, F.C.; Technau, G.M. (Development, 2002)
The gene spalt is expressed in the embryonic central nervous system of Drosophila melanogaster but its function in this tissue is still unknown. To investigate this question, we used a combination of techniques to analyse spalt mutant embryos. Electron microscopy showed that in the absence of spalt, the central nervous system cells are separated by enlarged extracellular spaces populated by membranous material at 60% of embryonic development. Surprisingly, the central nervous system from slightly older embryos (80% of development) exhibited almost wild-type morphology. An extensive survey by laser confocal microscopy revealed that the spalt mutant central nervous system has abnormal levels of particular cell adhesion and cytoskeletal proteins. Time-lapse analysis of neuronal differentiation in vitro, lineage analysis and transplantation experiments confirmed that the mutation causes cytoskeletal and adhesion defects. The data indicate that in the central nervous system, spalt operates within a regulatory pathway which influences the expression of the beta-catenin Armadillo, its ligand N-Cadherin, Notch, and the cell adhesion molecules Neuroglian, Fasciclin 2 and Fasciclin 3. Effects on the expression of these genes are persistent but many morphological aspects of the phenotype are transient, leading to the concept of sequential redundancy for stable organisation of the central nervous system.